Adsorption and catalytic ozonation performance of activated carbon and cobalt‐supported activated carbon derived from brewing yeast. (9th August 2013) - Wu, Guiping; Wei, Wei; Cui, Longzhe
Abstract Activated carbon (AC) was prepared from brewing yeast by Na<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr6x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives>CO<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr5c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives> activation, and cobalt was supported on activated carbon (Co/AC) by the adsorption–activation method. The XPS test indicated that supported cobalt was Co(II). The total BET surface areas of prepared AC and Co/AC were 957.7 and 847.9 m<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr81" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives>/g, with total pore volumes of 0.81 and 0.80 cm<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr7g" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>/g, respectively. The average pore diameters of AC and Co/AC were found to be 3.8 and 3.3 nm. The contact time required for equilibrium of methylene blue (MB) adsorption onto prepared AC and Co/AC was about 120 min. The maximum uptake of MB by AC and Co/AC was estimated to be 372.1 and 213.5 mg/g, respectively. The presence of prepared AC or Co/AC was advantageous for TOC reduction compared with UV/O<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr2q" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives> system, and the greatest TOC removal was obtained in the presence of Co/AC. The kinetics of the degradation of MB fitted the Langmuir‐first‐order model well. The rate constants of Langmuir first‐order were determined to be 0.0096 min−1 for UV/O<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr15" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>/AC and 0.0143 min−1 for UV/O<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg40fsnr38" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>/Co/AC, respectively.